Factors associated with depression during pregnancy in women receiving high- and low-risk prenatal care: a predictive model - Albertini, Jessica Gorrão Lopes; Benute, Glaucia Rossana Guerra; Francisco, Rossana Pulcineli Vieira; Galletta, Marco Aurélio Knippel (Frontiers in Psychiatry, 2024)
The present study presents data on the prevalence of depression during pregnancy in Brazilian pregnant women at high and low obstetric risk, assessed using the PRIME-MD, a more reliable instrument because it considers the clinical diagnosis according to the DSM-5. It also brings a predictive model for this diagnosis in pregnancy. Thus, it is of interest to psychiatrists who are concerned with perinatality, providing data that allow greater discussion on the repercussion of clinical and obstetric complications with antenatal depression.